Analysis of yeast chromosomal regions carrying members of the glutamate tRNA gene family: various transposable elements are associated with them. - Hauber, J (1988)
We carried out an analysis on the genomic organisation of the tRNA(Glu) family in S. cerevisiae; eight clones were characterized by restriction mapping, hybridization and sequencing. These data taken together with our earlier findings show that the individual tRNA(Glu3) copies are identical only in their structural part but embedded in entirely different genomic environments. All of the tRNA genes identified here are flanked by elements such as Ty, delta, sigma, and tau. In some cases, sequences from different elements form complex patterns indicating a sophisticated history of these chromosomal regions. A novel observation is that Ty and delta in the regions analyzed are exclusively associated with the tRNA genes. The observed patterns imply that the tRNA genes mark regions of multiple transposition and subsequent excision events, but that these have occurred after the individual tRNA gene copies had been fixed in their present locations. Transcription experiments by the use of micro-injection into Xenopus oocytes suggest that the elements flanking the tRNA genes exert a modulating effect on their expression.